Evangelicals on public policy issues : sustaining a respectful political conversation - Heie, Harold, 1935- (Abilene Christian University Press, 2014)
Six politically diverse evangelical Christians model a better way to do politics: respectful conversation about twelve public policy issues that uncover common ground and illuminate remaining disagreements. Current political discourse is broken, characterized by nasty sound bytes, demonizing the opposition, and holding to fixed positions that resist the discovery of the common ground needed for governing. In this volume six evangelical Christians model a better way, informed by the belief that the call of Christians to love their neighbors should create a welcoming space for persons to talk respectfully about their disagreements. The six Christians, who situate themselves at various points along the political spectrum, completed a nine-month "Alternative Political Conversation" on the website www.respectfulconversation.net on the following topics: the federal budget deficit, immigration, religious freedom, Syria and Iran, Israel and Palestine, poverty in the US, marriage, health care, K-12 education, gun control, abortion, and the role of government